Dialogue as a form of cooperation and coexistence. (Eurasian Journal of Philology Science and Education, 2015)
The article deals with the problem of cooperation between the states and the problems of civilization as a whole. Each new century or millennium, as each new dawn, sunrise, or the arrival of spring brings with it a new hope and marks a new beginning. In this respect, humanity for all time, over which we have no control, was always looking for a new spark of life, a fresh breath of the morning breeze striving to attain light instead of darkness as easy as crossing the threshold. The article also examines the problem of the in-deep realization of what i s going on, that must be taken into account as a number of factors of local, regional and global character. The problems of human rights are revealed as the sharpest in the dialogue between the West and the Muslim world. These questions are closely related to another factor that deserves attention. The whole complex of these problems causes particular interest and appears in a spotlight at rognostication of the development of countries in the near future. This theme is actual to date.
Keywords: dialogue; human consciousness; philosophy; civilization; culture and tolerance; democracy; islamic traditions; value; institutes; productivity; context; priority; compromise